Extracellular ATP regulates FoxO family of transcription factors and cell cycle progression through PI3K/Akt in MCF-7 cells - Scodelaro Bilbao, Paola; Boland, Ricardo (Biochimica et biophysica acta, 2013)
Forkhead Box-O (FoxO) transcription factors regulate the expression of many genes involved in suppression. Released nucleotides can regulate intracellular signaling pathways through membrane-bound purinergic receptors, to promote or prevent malignant cell transformation. We studied the role of extracellular ATP in the modulation of Forkhead Box O (FoxO) transcription factors and of cell cycle progression in MCF-7 breast cancer cells. Western blot analysis, cell transfections with siRNA against Akt, immunocytochemistry, subcellular fractionation studies and flow cytometry analysis were performed. ATP induced the phosphorylation of FoxO1/3a at threonine 24/32, whereas reduced the expression of FoxO1. In addition, ATP increased the expression of the cyclins D1 and D3 and down-regulated the cell cycle inhibitory proteins p21Cip1 and p27Kip1. The use of the phosphatidylinositol 3 kinase (PI3K) inhibitor, Ly294002, and/or of siRNA to reduce the expression of the serine/threonine kinase Akt showed that these effects are mediated by the PI3K/Akt signaling pathway. ATP induced the translocation of FoxO3a from the nucleus to the cytoplasm. Also, ATP increased the number of cells in the S phase of cell cycle; this effect was reverted by the use of Ly294002 and the proteasome inhibitor bortezomib. Extracellular ATP induces the inactivation of FoxO transcription factors and cell cycle progression through the PI3K/Akt pathway in MCF-7 cells. These findings provide new molecular basis for further understanding the mechanisms involved in ATP signal transduction in breast cancer cells, and should be considered for the development of effective breast cancer therapeutic strategies. •Extracellular ATP inactivates FoxO1/3a transcription factors in MCF-7 cells.•Extracellular ATP induces cell cycle progression of MCF-7 breast cancer cells.•The PI3K/Akt signaling pathway regulates both effects mediated by ATP.